(Increasing the Vetiverol Content of vetiver Oil by Rectification) - Sudibyo, Agus; Bastaman, Syarief; -, Hendarti (Warta Industri Hasil Pertanian, 1987)
A study on rectification of vetiver oil had been conducted in order to improve its quality and eugenol content. Retification was done by distillation using low vacuum pressure (15 and 20 mm Hg) and resulted in four fraction of vetiver oil (fraction I, II, III, IV). Observation which included chemical analysis (ester number, ester number after acetylation and vetiverol content) and physical analysis (refractive index at 20 degree) was done only on fraction III and IV. Research result showed that rectification improve the quality of vetiver oil. The vetiverol content of fraction III was increased by 8,10-9,35%, while those of fraction IV was 18,05-19,23%.